2017
DOI: 10.1016/j.envpol.2017.01.051
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthesis and aboveground carbon allocation of two co-occurring poplar species in an urban brownfield

Abstract: Phytoremediation, a technique used to reclaim heavy metal-contaminated soils, requires an understanding of plant physiological responses to heavy metals. However, the majority of studies documenting heavy metal impact on plant functioning have been performed in laboratory or greenhouse settings. We predicted that increased soil heavy metal concentrations reduce photosynthesis and biomass production in trees growing in metal contaminated soil in a naturally re-vegetated urban brownfield. Leaf gas exchange, leaf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 77 publications
(126 reference statements)
2
3
0
Order By: Relevance
“…A molecular approach, analyzing gene copies of different genes involved in N cycling, may reveal more details on which processes have been affected (Hallin et al 2009;Wallenstein and Vilgalys 2005). Previous studies on trees in heavy metal polluted mine tailing soil and an industrial urban soil also found a depletion in 15 N (Parraga-Aguado et al 2014;Radwanski et al 2017), which is in agreement with our finding in this study. On the contrary, in a forest soil surrounding a copper smelter, various tree and herbaceous species classified according to their mycorrhizal association showed an increase in 15 N, which was linked to increased rooting depth and/or a decrease in mycorrhizal formations (Chashchina et al 2018).…”
Section: Negative Impact On Microbial Biomass and Activitysupporting
confidence: 92%
See 1 more Smart Citation
“…A molecular approach, analyzing gene copies of different genes involved in N cycling, may reveal more details on which processes have been affected (Hallin et al 2009;Wallenstein and Vilgalys 2005). Previous studies on trees in heavy metal polluted mine tailing soil and an industrial urban soil also found a depletion in 15 N (Parraga-Aguado et al 2014;Radwanski et al 2017), which is in agreement with our finding in this study. On the contrary, in a forest soil surrounding a copper smelter, various tree and herbaceous species classified according to their mycorrhizal association showed an increase in 15 N, which was linked to increased rooting depth and/or a decrease in mycorrhizal formations (Chashchina et al 2018).…”
Section: Negative Impact On Microbial Biomass and Activitysupporting
confidence: 92%
“…Furthermore, Pb is a metal which generally accumulates in roots, with very little translocation to shoots (Siedlecka 1995). Thus, despite detecting various negative effects of Pb on nutrient cycling, the slowly adapted ecosystem as a whole seems to be able to bear strong resistance to contamination, as previously reported (Radwanski et al 2017;Rantalainen et al 2006;Selonen and Setälä 2015).…”
Section: Methodological Considerationsmentioning
confidence: 69%
“…However, specific leaf mass differences were. As in the former studies [47,63], both B. populifoloia and P. deltoids exhibited less mass per unit leaf area in areas of high soil metal loads. One plausible explanation is that there is a cost to production of phytochelatin enzymes, which are known to play a role in the detoxification of the metals once translocated [64].…”
Section: Functional Costs Of Metal Transfer and Tolerancesupporting
confidence: 66%
“…Therefore, despite being beyond the scope of the current study, ∆-assisted, multi-trait selection of productive clones should be carefully considered in future efforts, focusing on both growth and high WUE [ 51 , 57 ]. Such efforts are important, as they take into account linkages between WUE and phytoremediation that are associated with potential stress impacts from landfill soil properties and contamination sources [ 10 , 31 , 32 , 33 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, water use efficiency (WUE), which is strongly correlated with both δ 13 C stable carbon isotope ratios and carbon isotope discrimination (Δ) [ 29 , 30 ], is an important trait during genotype selection for phytoremediation. However, research using Δ in phytoremediation with trees is scarce [ 31 ], especially when considering potential stress impacts that are caused by landfill soil properties [ 32 , 33 ] and/or highly variable contamination sources [ 10 , 34 , 35 ] on plant water regimes during phytoremediation processes.…”
Section: Introductionmentioning
confidence: 99%